The Short-term Efficacy of Subthreshold Micropulse Yellow (577-nm) Laser Photocoagulation for Diabetic Macular Edema - Kwon, Yoon Hyung; Lee, Dong Kyu; Kwon, Oh Woong (Korean journal of ophthalmology, 2014)
This pilot study aimed to evaluate the efficacy and safety of subthreshold micropulse yellow (577-nm) laser photocoagulation (SMYLP) in the treatment of diabetic macular edema (DME). We reviewed 14 eyes of 12 patients with DME who underwent SMYLP with a 15% duty cycle at an energy level immediately below that of the test burn. The laser exposure time was 20 ms and the spot diameter was 100 µm. Laser pulses were administered in a confluent, repetitive manner with a 3 × 3 pattern mode. The mean follow-up time was 7.9 ± 1.6 months. The baseline-corrected visual acuity was 0.51 ± 0.42 logarithm of the minimum angle of resolution (logMAR), which was improved to 0.40 ± 0.35 logMAR (p = 0.025) at the final follow-up. The central macular thickness at baseline was 385.0 ± 111.0 µm; this value changed to 327.0 ± 87.7 µm (p = 0.055) at the final follow-up. SMYLP showed short-term efficacy in the treatment of DME and did not result in retinal damage. However, prospective, comparative studies are needed to better evaluate the efficacy and safety of this treatment.